Capacitação em negociação com o uso de um ambiente virtual tridimensional: uma experiência no Second life - Cardoso, Paloma (Universidade do Vale do Rio dos Sinos, 2011)
This study presents the results of research involving the metaverse Second Life as a resource for training in negotiation. The objective of this research was to understand how the metaverse Second Life can be constituted as a learning environment conducive to the development of negotiating skills. As a research method was developed a dynamic trading environment in Second Life through a case study with a qualitative approach, data were collected through interviews, telephone and virtual, fully transcribed for content analysis. The results revealed that these innovative approaches is feasible for training in negotiation.
Keywords: Metaverso; Second Life; Capacitação; Negociação; Metaverse; Second Life; Training; Negotiation